Patient and public involvement in Paediatric Intensive Care research: considerations, challenges and facilitating factors. Issue 1 (December 2016) - Menzies, J.; Morris, K.; Duncan, H.; Marriott, J.
Plain English summary Paediatric Intensive Care (PIC) provides care to extremely ill children. Research in this area can be difficult because children are often too sick to discuss being involved in a study and parents are too upset about their child to think about taking part. This makes it even more important that research is well designed. We conducted a review of the literature about involving patients and the public (PPI) in PIC research. We wanted to know what PPI has taken place, who had been consulted and how this was undertaken. We reviewed the titles and abstracts of 4717 papers but found only 4 relevant papers. Three of the papers had consulted with parents of children who had been on PIC but only one study had spoken directly to a child themselves. The studies had used a number of different methods to invite people to take part but there did not appear to be one solution. All of the studies thought PPI was good for the development of their research but none of them had tried to measure what had changed as a result. There are difficulties associated with carrying out PPI in the PIC setting. Researchers need to share more of their experiences, positive and negative, so we can try to identify the best ways of carrying out PPI in PIC studies. This will help ensure that research studies are designed which address the needs and concerns of children and their parents. Abstract Introduction Involving the public in health care research is reported to enhance the quality, appropriateness, acceptability and relevance to patients and the public (INVOLVE, Briefing notes for researchers, 2012; Staniszewska et al., Int J Technol Assess Health Care 274:391-9, 2011). Conducting research with children and young people is regarded as challenging and this makes it even more important that the research is well designed and understands the perspective of the child and family. We conducted a narrative literature review of the Patient and Public Involvement (PPI) literature, in the context of Paediatric Intensive Care (PIC). Our aims were to identify what PPI activity has taken place, with whom researchers engaged and what outcomes they reported. Method Electronic databases Medline, CINAHL and Embase (January 2000- June 2016) were searched using the search terms patient and public involvement and consultation. Participants were defined as child, parent, paediatric or pediatric and the context as intensive or critical care. Papers were excluded where activity reflected 'participants' as research subjects. Included papers were reviewed using the GRIPP checklist to appraise the quality of reporting. Results The search strategy identified 4717 abstracts. Seventeen papers were reviewed in full and four papers were included, all of which are case studies, describing a consultation approach. None of the papers described PPI as a multi-stage process. Only one study engaged with a former PIC patient and the majority of those consulted did not have any PIC experience. Activity was reported as being of benefit but there was no measurement of the impact of PPI. Conclusion There are numerous challenges associated with the conduct of research in PIC. It is therefore essential that the perspective of children, young people and their parents have been considered in the design of trials. However, there are few published accounts of PPI within the PIC context and the accounts that exist highlight issues about who to approach and when, and a lack of clarity about the best ways to engage with them. Research Ethics Committees and funding bodies expect to see evidence of PPI in research applications and we need to develop our understanding of what contributes towards successful PPI in this context.